A new genus and twenty new species of Australian jumping plant-lice (Psylloidea: Triozidae) from Eremophila and Myoporum (Scrophulariaceae: Myoporeae) - Taylor, Gary S.; Fagan-Jeffries, Erinn P.; Austin, Andy D. (Zootaxa, 2016)
The Triozidae is a diverse, cosmopolitan family of jumping plant-lice (Hemiptera: Psylloidea) from an exceptionally diverse range of plant families, but with few described Australian species. As a direct outcome of the Australian Biological Resources Study Bush Blitz species discovery program, many new Psylloidea from novel host plants in remote localities have been revealed. In this study a new genus Myotrioza Taylor gen. nov. and 20 new species are described from southern and central Australia which also establishes the first host plant records from Eremophila and Myoporum (Scrophulariaceae: Myoporeae). New species, delineated using a combination of morphological and mitochondrial COI sequence data, are: Myotrioza clementsiana sp. nov., M. darwinensis sp. nov., M. desertorum sp. nov., M. eremi sp. nov., M. eremophili sp. nov., M. flindersiana sp.nov., M. gawlerensis sp. nov., M. insularis sp. nov., M. interioris sp. nov., M. interstantis sp. nov., M. longifoliae sp. nov., M. markmitchelli sp. nov., M. myopori sp. nov., M. oppositifoliae sp. nov., M. pantonii sp. nov., M. platycarpi sp. nov., M. remota sp. nov., M. scopariae sp. nov., M. serrulatae sp. nov., and M. telowiensis sp. nov. Genetic divergence data, host associations, biogeographic data, diagnoses and a key to species are presented. Myotrioza appears to be particularly diverse in ephemeral southern Australia, especially in inland Western Australia and South Australia, matching regions of high diversity of the host genera; some species are likely to be short range endemics.